Antibacterial properties of bentonite based zeolite a ion exchanged with silver and copper against marine bacterial pathogens - Nur Ariffah Waly (2020)
Development of aquaculture industry has been increasing rapidly around the world. However, this development is facing a great challenge due to bacterial disease outbreaks, leading to high mortality rates of the aquaculture population. Attempts to overcome this problem has resulted in a new greater challenge of antimicrobial resistance of bacteria due to broad usage of antibiotics. Therefore, the development of inorganic antibacterial agent, through the synthesis of bentonite based Zeolite A, further integrated with Ag and Cu? via ion exchange was hence proposed as an alternative to combat the bacteria. The bentonite clay as Si-Al source for zeolite synthesis was thermally transformed into an active phase at 100 ·C for 24 hours in the presence of concentrated hydrochloric acid, followed with the preparation of zeolite A mixture. Mixture of Zeolite A was prepared by using 2.5NaO: Al5Os: 1.5Si0,: 166H0 molar ratio. Hydrothermal synthesis of Zeolite A was carried out by aging process for 30 minutes followed by crystallization for 8 hours at 100 C and it was found that the optimum silica to alumina ratio and molarity of NaOH for the synthesis was 1.50 and 2.50 M respectively. Subsequently, the Zeolite A product underwent ion-exchange process with Ag and Cu?'and the metal content of ion-exchanged zeolite was determined by ICP-OES. The results obtained shows that pH and concentration of metal ion solution played important parts in ion-exchange process. The highest Cu? content was found on Zeolite A that was treated with 1.50 M of copper solution at pH 6 which is equal to 93.630 ± 1.114 (mg/g). Meanwhile, the highest Ag+ content was found on Zeolite A that was introduced to 1.50 M of silver solution at pH 6 which is equal to 190.511 ± 1.989 (mg/g). Antibacterial activity of the Ag (Ag?) and Cu?' (CuZ) ionexchanged zeolite A samples against V. campbellii and V. parahaemolyticus were evaluated by determining the Minimum Inhibition Concentration (MICs) using twofold serial dilutions of ion loaded zeolites in Tryptic Soy broth (TSB) supplemented with 2% of NaCl. The concentrations for AgZ and CuZ ranged from 0.125 mg/ml - 2.00 mg/ml and 5.00 mg/ml - 25.00 mg/ml respectively. The resulting results obtained shows that, the highest metal ion content zeolite A gives the lowest MICs value. The highest silver ion content in zeolite A needed to inhibit the growth of V. campbe/lii and V. parahaemolyticus was 0.125 mg/ml and 0.0625 mg/ml respectively. Consequentially, the amount of copper ion content zeolite required for bacterial inhibition was 6.25 mg/ml for V. campbellii and 5.00 mg/ml for V. parahaemo!yticus, which inherently were higher compared to the MICs value of silver ion content zeolite. The ability of the AgZ and CuZ to inhibit the biofilm formation was then studied by Crystal Violet Biofilm Inhibition Assay. Based on this assay, the percentage biofilm inhibition (BI) of AgZ and CuZ were obtained where, the CuZ gives 39.18% and 43.49% BI against V. campbellii and V parahaemolyticus correspondingly. Accordingly, AgZ shows 60.24% BI against IV, campbellii and 77.32% BI against V. parahaemolyticus. Therefore, due to its significant antibacterial performance, Ag and Cu? ion-exchanged zeolite has great potential to be used as an alternative to the organic antibiotics, especially in the aquaculture industry.